Myasthenia Gravis - Drachman, Daniel B. (Seminars in Neurology, 2016)
The basic abnormality in myasthenia gravis (MG) is a reduction in acetylcholine receptors (AChRs) at neuromuscular junctions due to the effects of autoantibodies that are directed against the AChRs in most patients, or against neighboring proteins involved in the clustering of AChRs (MuSK, LRP-4, or agrin). Clinically, MG is characterized by muscle weakness and fatigue, often in typical patterns. The diagnosis may be missed early, and depends on the recognition of clinical manifestations, the measurement of autoantibodies, and/or electrophysiological features. The treatment of MG involves the enhancement of neuromuscular transmission by anticholinesterase drugs (pyridostigmine), and by immunotherapy. Therapy should be designed to improve the clinical features quickly, and keep the symptoms in abeyance over the long term. Rapid improvement can be achieved when necessary by the administration of intravenous immunoglobulin or plasma exchange. Intermediate rates of improvement over months involve the use of adrenal corticosteroids, the calcineurin inhibitors cyclosporine or tacrolimus, and in some patients, the B-cell inhibitor rituximab. For long-term treatment, mycophenolate and azathioprine are the most effective agents. A thymectomy may also have long-term beneficial effects. The majority of MG patients can live normal lives, but most patients require lifelong treatment. The physician's skill in managing the immunotherapeutic agents and avoiding adverse side effects is of paramount importance in the treatment of MG.
Keywords: myasthenia gravis; acetylcholine receptors; autoimmunity; antibodies; immunotherapy